Rural youth and public higher education: student trajectories of a public university campus of the northeast of Brazil - Melo, Samuel Pires; Braga, Osmar Rufino; Santana, Jullyane Frazão (Universidade Estadual de Campinas, 2019)
In recent years, there has been a process of internalization of higher education in Brazil, resulting mainly from the public policy of restructuring and expansion of federal universities, instituted in 2007. However, to what extent this process can be considered as changes in life trajectories of historically marginalized social groups? To trigger such a discussion, this article analyzes the school trajectories of young rural students from a public university campus in northeastern Brazil. This is a quantitative, descriptive study with random sampling of students from the exact and biological sciences courses, in which the questionnaire and field diary were used as data collection instruments; descriptive statistics and content analysis, as procedures for analyzing these data. The results pointed to a profile of young people ranging in age from 18 to 33 years; school trajectory of migration to city spaces, as motivation to continue studies due to the precariousness of education in rural spaces; and future prospects for higher education aiming at the financial rise to help the family and its territories. Therefore, this study suggests that the internalization and expansion programs of federal universities are being an ally in the changing trajectories of young people in rural areas.